Exploring national parks and the Big Nine: A Literature review approach - Kimeto, Janet c.; Mkwizu, Kezia H. (Bahasa Indonesia, 2024)
The ‘Big Five’ are considered to be the Lion, Leopard, Rhino, Buffalo and Elephant which have become synonymous with Africa’s safaris in the national parks. Guided by the Butler’s TALC model, this paper aims to compare national parks development focusing on the ‘Big Nine’ in Kenya and Tanzania. Specifically, this paper explores national parks conservation and management in relation to the ‘Big Nine’. The method used is the Systematic Literature Review (SLR), whereby 16 journal articles were found to be relevant for the study were analyzed. The finding shows that for the future generations, the ‘Big Five’ requires protection and conservation in the national parks, other wild animals like Zebras and Warthogs included. The outcome of this paper advocates for other diverse wild animals in Kenya and Tanzania that could fascinate tourists be included in the “Big Five” to have either the ‘Big Seven’ or ‘Big Nine’. Future studies may opt for quantitative and qualitative approaches as mixed methods to further explore national parks and wild animals in Kenya and Tanzania as well as other African countries in the post-colonial era.